2014
DOI: 10.3168/jds.2013-7517
|View full text |Cite
|
Sign up to set email alerts
|

Bovine colostrum: Changes in lipid constituents in the first 5 days after parturition

Abstract: Despite the great interest paid to protein components in colostrum, fat also plays an important role in the supply of essential nutrients to provide energy, increase metabolism, and protect the newborn calf against microbial infections. This work aimed to elucidate levels of different fat components in colostrum, in particular fatty acid (FA), triglyceride (TG), cholesterol, and phospholipid contents. Colostrum samples from primiparous and multiparous (3-5 lactations) Holstein dams, fed the same ration indoors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
53
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 32 publications
14
53
2
15
Order By: Relevance
“…Previous studies showed that the ether extract concentration varied from 4.6 to 6.7% (Kehoe et al, 2007;Morril et al, 2012;Contarini et al, 2014) and similar values were observed in the present study. High-fat colostrum is desirable when there is a high demand for energy for the newborn, since calves are born with reduced energy reserves (Okamota et al, 1986) and have high energy requirements to maintain thermogenesis (Hammon et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies showed that the ether extract concentration varied from 4.6 to 6.7% (Kehoe et al, 2007;Morril et al, 2012;Contarini et al, 2014) and similar values were observed in the present study. High-fat colostrum is desirable when there is a high demand for energy for the newborn, since calves are born with reduced energy reserves (Okamota et al, 1986) and have high energy requirements to maintain thermogenesis (Hammon et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Ether extract content influences the volume of produced colostrum, although few changes occur in the first five days after calving (Contarini et al, 2014). Previous studies showed that the ether extract concentration varied from 4.6 to 6.7% (Kehoe et al, 2007;Morril et al, 2012;Contarini et al, 2014) and similar values were observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…When studying the lipid components of bovine colostrum in the first 5 days after calving, Contarini et al (2014) observed that the colostrum had a different fat composition in the first 24 hours than the fluid produced after four or five days and the milk of half lactation, highlighting an abundant concentration of essential lipids for the neonate such as omega-3 and phospholipids (mainly sphingomyelin) and cholesterol, while concentrations for trans fatty acids like linoleic-conjugated acid were lower in the first hours of production.…”
Section: Bovine Colostrum Compositionmentioning
confidence: 99%
“…Em propriedades com volume de produção superior a 700 litros/dia o teor de matéria seca, proteína bruta e imunoglobulinas foram superiores as propriedades com produção inferior a 200 L/dia e na classe de 201 a 700 L/dia (p<0,05) (Tabela 2 CONTARINI et al, 2014). Pesquisas mostraram concentração em extrato etéreo variando de 4,6 a 6,7% MORRILL et al, 2012;CONTATINI et al, 2014).…”
Section: Resultsunclassified